2014
DOI: 10.1007/s00268-014-2643-7
|View full text |Cite
|
Sign up to set email alerts
|

Impact on Liver Cancer Treatment of a First Erroneous Diagnosis of Hemangioma

Abstract: A false diagnosis of HA in the presence of malignancy is not rare nowadays and significantly reduces the chances of cure. In situations at risk of having the error occur (poor technical quality of imaging, low specific experience, doubtful diagnosis, and high-cancer-risk patient), the rationale approach is to discuss the case with a multidisciplinary team skilled in the field of liver cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 25 publications
(36 reference statements)
0
4
0
Order By: Relevance
“…Second, the misconception that a proper USG examination is adequate for the diagnosis of a hemangioma and further examination is unnecessary ( 16 , 17 ). Only 80 % of the liver hemangiomas have a typical appearance on USG ( 18 , 19 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Second, the misconception that a proper USG examination is adequate for the diagnosis of a hemangioma and further examination is unnecessary ( 16 , 17 ). Only 80 % of the liver hemangiomas have a typical appearance on USG ( 18 , 19 ).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, in the study by Portolani et al, 75% of the incorrect diagnoses were made at low volume centers. A high-volume center was “characterized by the availability of an interdisciplinary group for the management of liver disease, by a tertiary-level or an academic hospital, or by the certification of almost 40 liver resections per year” ( 16 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…11.2 ). a b Recently, Portolani et al [ 21 ] analyzed 28 patients with liver cancer who were observed after an initial erroneous diagnosis of hemangioma. The authors reported that the majority of the incorrect diagnoses (75 %) came from low volume center and occurred more frequently with the small nodules in chronic liver disease.…”
Section: Evolutionmentioning
confidence: 99%